Thermally conductive resin composition and thermally conductive sheet

By using addition reactive silicone resin, thermal filler, alkoxysilane and dimethylpolysiloxane in the thermally conductive resin composition, the thermally conductive resin composition is solved by the thermally conductive resin composition to resist heat at high temperatures in the prior art. The problem of poor reliability achieves a balance between high thermal conductivity and low cost, and is suitable for efficient cooling applications in the automotive industry.

CN119307099APending Publication Date: 2025-01-14SEKISUI CHEMICAL CO LTD

Patent Information

Application Number
CN202410886260.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-11
Filing Date
2024-07-03
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing thermal conductivity resin compositions have poor heat resistance and reliability at high temperatures, and it is difficult to achieve both high thermal conductivity and low cost. Especially in applications used in the automotive industry for cooling components such as inverters, the thermal conductivity of existing materials The performance is not enough to meet the improvement of fuel economy performance.

Method used

The combination of addition reactive silicone resin, thermal conductivity filler, alkoxysilane and dimethylpolysiloxane having two or more hydroxyl groups at the single end of the molecular chain can improve thermal conductivity by optimizing the type and proportion of fillers. The kneading and heat resistance of the elastic resin composition were prepared to produce a thermally conductive resin composition and sheet with a high thermal conductivity coefficient.

Benefits of technology

The thermally conductive resin composition is achieved with good kneading, low viscosity and high thermal conductivity, and good flexibility and heat resistance are maintained under high temperature environments. The thermal conductivity coefficient of the thermally conductive sheet reaches 4.0W/(m· K) Above, the hardness of ASKER C is not likely to increase significantly at 170°C, meeting the automotive industry's demand for efficient cooling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307099A_ABST
    Figure CN119307099A_ABST
Patent Text Reader

Abstract

Provided are a thermally conductive resin composition and a thermally conductive sheet which have excellent heat resistance and reliability. The thermally conductive resin composition contains an addition reaction type silicone resin, a thermally conductive filler, an alkoxysilane, and a dimethyl polysiloxane having two or more hydroxyl groups at one end of a molecular chain. The thermally conductive sheet includes a cured product of a thermally conductive resin composition containing an addition reaction type silicone resin, a thermally conductive filler, an alkoxysilane, and a dimethyl polysiloxane having two or more hydroxyl groups at one end of a molecular chain.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present technology relates to a thermally conductive resin composition and a thermally conductive sheet. Background Art

[0002] Generally, thermal interface materials are composite materials formed by dispersing thermally conductive fillers in resins such as epoxy resins and silicone resins. Metal oxides are often used as thermally conductive fillers. However, the thermal conductivity of sheet-like molded bodies formed from composite materials using metal oxides in the thickness direction remains at around 1 to 3 W / (m·K). Therefore, sheet-like molded bodies with higher thermal conductivity are required. For example, a method of highly filling a thermally conductive filler with higher thermal conductivity in a thermally conductive resin composition can be considered. Commonly used thermally conductive fillers include: aluminum oxide, aluminum nitride, zinc oxide, magnesium oxide (magnesium oxide), aluminum hydroxide, boron nitride, and the like.

[0003] As awareness of global warming increases, the automotive industry is advancing the development of environmentally friendly vehicles such as hybrid vehicles, plug-in hybrid vehicles, and electric vehicles in order to reduce greenhouse gases. In order to further improve the fuel economy of these environmentally friendly vehicles, the inverters installed in the vehicles are becoming more high-performance and smaller. As a result, components such as ICs (Integrated Circuits) and reactors in the inverters are also miniaturized, and the heat generation is further increased.

[0004] For such a heat-generating component, for example, the following method can be cited: a heat-conductive silicone composition such as a heat-conductive silicone grease composition, a heat-conductive silicone gel composition, a heat-conductive silicone potting composition, etc. of about 1 to 3 W / (m·K) is sandwiched between the heat-generating component and the cooler, thereby improving the cooling efficiency of the component and protecting the component (for example, refer to Patent Document 1). However, in order to further increase the heat generation, it is required to develop a heat-conductive resin composition of 5 W / (m·K) or more. At the same time, it is also required to achieve a high thermal conductivity and low manufacturing cost.

[0005] In order to obtain a thermally conductive resin composition that is cheap and can achieve a high thermal conductivity, for example, it is possible to consider not using aluminum nitride and aluminum powder that have been used in the past as much as possible, and to use more metal oxides such as crushed aluminum oxide that are cheaper as thermally conductive fillers. However, metal oxides such as crushed aluminum oxide have lower thermal conductivity than aluminum nitride and aluminum powder, so it is considered that in order to use more metal oxides such as crushed aluminum oxide and achieve a high thermal conductivity, it is necessary to further increase the total amount of thermally conductive fillers in the thermally conductive resin composition. In order to increase the filling amount of the thermally conductive filler in the thermally conductive resin composition, alkoxysilane is sometimes used.

[0006] The thermally conductive resin composition generally contains alkoxysilane; ionic components brought by the thermally conductive filler, metal components, and organic compounds containing elements such as N, P, and S. It is believed that if the filling amount of the thermally conductive filler in the thermally conductive resin composition reaches about 65% by volume, the influence of the above substances (alkoxysilane; ionic components, metal components, and organic compounds containing elements such as N, P, and S) can also be ignored.

[0007] However, alkoxysilane is hydrolyzable, and the hydrolysis of alkoxysilane, the dehydration condensation following the hydrolysis, the volatilization of unreacted components, etc., may promote the reduction of the heat resistance reliability of the thermally conductive resin composition along with the use at high temperature. In addition, for example, in a thermally conductive composition with an addition polymerization type silicone resin as a binder component, the above-mentioned ionic components and metal components may become the main cause of the following situation: hindering the platinum catalyst that is a catalyst for the polymerization reaction of the addition polymerization type silicone resin. At this time, the silicone resin that does not contribute to the polymerization may be oxidized (aged) at high temperature. Moreover, after the curing of the thermally conductive resin composition, the silicone resin that does not contribute to the polymerization may undergo reactions such as depolymerization, resulting in a reduction in heat resistance reliability.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent Application Publication No. 2021-113290

[0011] Patent Document 2: Japanese Patent No. 6610429

[0012] Patent Document 3: Japanese Patent No. 6613462

[0013] Patent Document 4: Japanese Patent Application Publication No. 2021-176945

[0014] The present technology has been proposed in view of such existing actual conditions, and provides a thermally conductive resin composition and a thermally conductive sheet having excellent heat resistance reliability. Summary of the invention

[0015] The thermally conductive resin composition of the present technology contains an addition reaction type silicone resin, a thermally conductive filler, an alkoxysilane, and a dimethyl polysiloxane having two or more hydroxyl groups at one end of a molecular chain.

[0016] The thermally conductive sheet of the present technology includes a cured product of a thermally conductive resin composition containing an addition reaction type silicone resin, a thermally conductive filler, an alkoxysilane, and a dimethyl polysiloxane having two or more hydroxyl groups at one end of a molecular chain.

[0017] Effects of the Invention

[0018] The present technology can provide a thermally conductive resin composition with good heat resistance and reliability. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a cross-sectional view showing an example of a semiconductor device to which a thermally conductive sheet is applied.

[0020] Description of Reference Numerals

[0021] 1: thermally conductive sheet; 50: semiconductor device; 51: electronic component; 52: heat sink; 52a: main surface; 52b: side wall; 52c: other surface; 53: heat sink. DETAILED DESCRIPTION

[0022] In this specification, the average particle size (D50) of the thermally conductive filler (hereinafter referred to as "average particle size") refers to the particle size when the cumulative value is 50% when the cumulative curve of the particle size value is obtained from the small particle size side of the particle size distribution, when the particle size distribution of the thermally conductive filler as a whole is set to 100%. It should be noted that the particle size distribution (particle size distribution) in this specification is obtained based on the volume basis. As a method for measuring the particle size distribution, for example, a method using a laser diffraction type particle size distribution measuring instrument can be cited.

[0023] <Thermal conductive resin composition>

[0024] The thermally conductive resin composition of the present technology contains: an addition reaction type silicone resin (hereinafter also referred to as "component a"), a thermally conductive filler (hereinafter also referred to as "component b"), an alkoxysilane (hereinafter also referred to as "component c"), and a dimethylpolysiloxane having two or more hydroxyl groups at one end of the molecular chain (hereinafter also referred to as "component d").

[0025] Here, the thermally conductive resin composition composed of component a, component b and component c has good kneading properties and can be made into a low viscosity. However, the thermally conductive resin composition composed of component a, component b and component c has poor heat resistance reliability. For example, when it is made into a thermally conductive sheet, when it is placed in an environment of 170°C for 1000 hours, it deteriorates rapidly and the hardness of the thermally conductive sheet (for example, Asker C hardness) increases by about 3 to 4 times.

[0026] Therefore, the thermally conductive resin composition of the present technology can have good heat resistance reliability by containing component d in addition to components a to c. The thermally conductive resin composition can have good kneading properties and can be made into a low viscosity even when a cheap thermally conductive filler (such as an irregularly shaped thermally conductive filler described later) is used by containing component d. In addition, the thermally conductive resin composition can also have good thermal conductivity and softness when made into a thermally conductive sheet by containing component d. Moreover, the thermally conductive resin composition can be made into a thermally conductive sheet by using components c and d in combination, and the heat resistance reliability of the thermally conductive sheet is not easy to deteriorate even after being put into an environment of 170°C for 1000 hours, and the hardness of the thermally conductive sheet (such as ASKER C hardness) can be suppressed. In this way, the thermally conductive resin composition of the present technology can maintain good softness even in a high temperature environment.

[0027] <Ingredient a>

[0028] In the thermally conductive resin composition of the present technology, as component a, a silicone resin is used as a binder resin because it has excellent molding processability and weather resistance and good adhesion and followability to electronic components. In particular, from the viewpoint of improving molding processability, weather resistance, and adhesion, it is preferred to use a silicone resin composed of a main agent of liquid silicone gel and a curing agent.

[0029] Examples of such silicone resins include addition reaction type silicone resins, heat-vulcanized kneaded silicone resins (kneaded rubber) that are vulcanized using peroxides, etc. In particular, when the thermally conductive resin composition is applied to a thermally conductive sheet sandwiched between a heat generating body and a heat dissipating member, for example, adhesion between the heat generating surface of an electronic component and the surface of a heat absorbing device is required, and therefore addition reaction type silicone resins (addition reaction type liquid silicone resins) are preferred.

[0030] Examples of the addition reaction type silicone resin include a two-component addition reaction type silicone resin comprising (i) silicone having an alkenyl group as a main component, (ii) a main agent containing a curing catalyst, and (iii) a curing agent having a hydrosilyl group (Si—H group).

[0031] As (i) an organosilicon having an alkenyl group, for example, a polyorganosiloxane having a vinyl group can be used. (ii) A curing catalyst is a catalyst for promoting the addition reaction of the alkenyl group in the organosilicon having an alkenyl group (i) and the hydrosilyl group in the curing agent having a hydrosilyl group (iii). As (ii) a curing catalyst, catalysts known as catalysts used in hydrosilylation reactions can be cited, for example, platinum group curing catalysts can be used, such as platinum group metal single substances such as platinum, rhodium, and palladium, platinum chloride, etc. As (iii) a curing agent having a hydrosilyl group, for example, a polyorganosiloxane having a hydrosilyl group can be used. By adopting such a structure, it is easy to highly fill component b, and the curing temperature can also be easily adjusted by a catalyst or the like.

[0032] Considering the hardness of the cured product obtained by curing the thermally conductive resin composition, the addition reaction type silicone resin can use a desired commercial product, for example. Commercial products of the addition reaction type silicone resin include, for example: CY52-276, CY52-272, EG-3100, EG-4000, EG-4100 (all manufactured by Dow Toray), KE-1800T, KE-1031, KE-1051J (all manufactured by Shin-Etsu Chemical Co., Ltd.), etc. The addition reaction type silicone resin can be used alone or in combination of two or more.

[0033] <Ingredient b>

[0034] The thermally conductive resin composition of the present technology contains a thermally conductive filler as component b. Component b is dispersed in component a. Component b can be selected from known substances in view of the desired thermal conductivity and filling properties, for example: metal hydroxides such as aluminum hydroxide and magnesium hydroxide; metals such as aluminum, copper, and silver; metal oxides such as aluminum oxide and magnesium oxide; metal nitrides such as aluminum nitride, boron nitride, and silicon nitride; carbon nanotubes; metal silicon; fiber fillers (glass fibers, carbon fibers). Component b can be used alone or in combination of two or more.

[0035] From the viewpoint of improving the thermal conductivity of the thermally conductive resin composition and reducing the production cost of the thermally conductive resin composition, it is preferred to avoid using relatively expensive thermally conductive fillers (such as aluminum nitride and aluminum) as much as possible and to use relatively cheap thermally conductive fillers (such as metal oxides such as aluminum oxide and magnesium oxide). For example, as component b, it is preferred to use at least one of magnesium oxide and aluminum oxide, preferably containing magnesium oxide, more preferably using aluminum oxide and magnesium oxide in combination, or it is also possible to use only aluminum oxide and magnesium oxide.

[0036] From the viewpoint of improving the thermal conductivity of the thermally conductive resin composition, the thermally conductive resin composition preferably contains a spherical thermally conductive filler as component b. Here, spherical means, in addition to a completely spherical shape, a substantially spherical shape, an elliptical shape, and the like, for example, the sphericity may be greater than 0.8. The average particle size of spherical magnesium oxide, as an example of a spherical thermally conductive filler, may be, for example, in the range of 0.1 to 150 μm, or in the range of 70 to 140 μm. In addition, the average particle size of spherical aluminum oxide, as an example of a spherical thermally conductive filler, may be, for example, in the range of 0.1 to 50 μm, or in the range of 5 to 25 μm.

[0037] Furthermore, from the viewpoint of reducing the production cost of the thermally conductive resin composition, the thermally conductive resin composition preferably contains an irregularly shaped thermally conductive filler as component b in addition to the spherical thermally conductive filler. That is, the thermally conductive resin composition preferably contains a spherical thermally conductive filler and an irregularly shaped thermally conductive filler as component b. The irregular shape refers to a shape that does not conform to a spherical shape and has an irregular shape and size, including flake-shaped, needle-shaped, polyhedral, and the like. For irregularly shaped thermally conductive fillers, for example, the secondary particles are more than 70% based on the number, and the secondary particles are formed by at least a portion of primary particles of a plurality of thermally conductive fillers having a crystalline phase and a grain boundary phase being mutually fused through the grain boundary phase. The average particle size obtained by a laser diffraction scattering method is less than 300 μm, and the ratio of the average particle size of the primary particles of the thermally conductive filler obtained by analyzing an image taken by a scanning electron microscope to the volume average equivalent circle diameter is within the range of greater than 2.8 and less than 5.0. Although the shape is irregular, the number of small-sized particles is less than that obtained by crushing bulk raw materials or large-sized particles, and therefore it is more preferred.

[0038] From the viewpoint of thermal conductivity, the irregularly shaped thermally conductive filler is preferably, for example, irregularly shaped magnesium oxide or irregularly shaped aluminum oxide. In addition, the average particle size of the irregularly shaped thermally conductive filler may be in the range of 0.1 to 150 μm, 10 to 150 μm, 0.1 to 50 μm, or 60 to 130 μm. The BET specific surface area of ​​the irregularly shaped thermally conductive filler may be 5 m 2 / g or less, or 1m 2 / g or less, and may be 0.1 to 5 m 2 / g range.

[0039] As an embodiment of component b, spherical alumina, irregular alumina, and spherical magnesium oxide may be used in combination, or spherical alumina, irregular alumina, and irregular magnesium oxide having a crystal phase and a grain boundary phase may be used in combination.

[0040] As described above, from the viewpoint of making the thermal conductivity of the thermally conductive resin composition good and reducing the manufacturing cost of the thermally conductive resin composition, it is preferred not to use more expensive thermally conductive fillers (such as aluminum nitride, aluminum) as much as possible, and more cheap thermally conductive fillers (such as metal oxides such as aluminum oxide and magnesium oxide) are used. However, the cheaper thermally conductive filler has lower thermal conductivity than the more expensive thermally conductive filler, so compared with the case of using only the more expensive thermally conductive filler, it is necessary to further increase the total filling amount of the thermally conductive filler. If such a viewpoint is taken into account, the content of component b in the thermally conductive resin composition can be set to 70 to 95% by mass, 75 to 95% by mass, 80 to 95% by mass, 85 to 95% by mass, or 90 to 95% by mass, for example, in terms of the mass content in the thermally conductive resin composition. If the content of component b in the thermally conductive resin composition is less than 70% by mass, there is a tendency that it is not easy to obtain sufficient thermal conductivity. In addition, if the content of component b in the thermally conductive resin composition is greater than 95% by mass, there is a tendency that it is difficult to make the kneading property good. When two or more thermally conductive fillers are used in combination, the total amount thereof preferably satisfies the above-mentioned content range.

[0041] Irregular-shaped thermally conductive fillers have a larger specific surface area than spherical thermally conductive fillers, so if a large amount of irregular-shaped thermally conductive fillers is used, there is a tendency that it is difficult to improve the kneading properties of the thermally conductive resin composition. Therefore, the content of the irregular-shaped thermally conductive filler is preferably 80% by mass or less relative to the total amount of component b in the thermally conductive resin composition.

[0042] <Ingredient c>

[0043] The thermally conductive resin composition of the present technology contains alkoxysilane (alkoxysilane compound) as component c. Alkoxysilane functions as a coupling agent (dispersant). Alkoxysilane is hydrolyzed to form silanol, which is bonded to the surface of the thermally conductive filler, and helps to make the dispersibility of the thermally conductive filler in the thermally conductive resin composition better.

[0044] Alkoxysilane is a compound having a structure in which, for example, one to three of four bonds of a silicon atom (Si) are bonded to an alkoxy group, and the remaining bonds are bonded to an organic substituent.

[0045] As the alkoxy group possessed by the alkoxysilane, for example, methoxy, ethoxy, propoxy, butoxy, pentyloxy and hexyloxy can be listed. Alkoxysilane can also be contained in the thermally conductive resin composition (or the thermally conductive sheet described later) in the form of a dimer. From the viewpoint of ease of acquisition, the alkoxysilane preferably has a methoxy group or an ethoxy group. From the viewpoint of further improving the affinity with the thermally conductive filler, the number of alkoxy groups possessed by the alkoxysilane is preferably three. As a specific example of alkoxysilane, it is preferably selected from at least one of a trimethoxysilane compound and a triethoxysilane compound.

[0046] The functional groups contained in the organic substituents possessed by the alkoxysilane include, for example, acryloyl, alkyl, carboxyl, vinyl, methacryloyl, aromatic groups, amino, isocyanate, isocyanurate, epoxy, hydroxyl, and mercapto. Here, for example, when an addition reaction type organopolysiloxane containing a platinum catalyst is used as the above-mentioned component a, the alkoxysilane is preferably an alkoxysilane that is not likely to affect the curing reaction of the organopolysiloxane. Specifically, when an addition reaction type organopolysiloxane containing a platinum catalyst is used, the organic substituent of the alkoxysilane preferably does not contain an amino, isocyanate, isocyanurate, hydroxyl, or mercapto.

[0047] From the viewpoint of further improving the dispersibility of the thermally conductive filler and making it easier to highly fill the thermally conductive filler, the alkoxysilane is preferably an alkylalkoxysilane having an alkyl group bonded to a silicon atom, i.e., an alkyl-containing alkoxysilane. In the alkyl-containing alkoxysilane, the number of carbon atoms of the alkyl group bonded to the silicon atom is preferably 4 or more, or 6 or more, or 8 or more, or 10 or more. In addition, from the viewpoint of further suppressing the viscosity of the thermally conductive resin composition, in the alkyl-containing alkoxysilane, the number of carbon atoms of the alkyl group bonded to the silicon atom is preferably 16 or less, or 14 or less, or 12 or less. In the alkyl-containing alkoxysilane, the alkyl group bonded to the silicon atom may be linear, branched, or cyclic.

[0048] As specific examples of alkoxysilane, compounds represented by the following formula A can also be mentioned.

[0049] (Formula A)

[0050] CH3(CH2) n SiX3

[0051] In formula A, n represents an integer of 5 to 15, and X represents a methoxy group or an ethoxy group. X in formula A may be of the same type or of different types.

[0052] Specific examples of alkoxysilanes include, in addition to alkyl-containing alkoxysilanes, vinyl-containing alkoxysilanes, acryl-containing alkoxysilanes, methacryloyl-containing alkoxysilanes, aromatic group-containing alkoxysilanes, amino-containing alkoxysilanes, isocyanate-containing alkoxysilanes, isocyanurate-containing alkoxysilanes, epoxy-containing alkoxysilanes, mercapto-containing alkoxysilanes, and the like. As the alkyl-containing alkoxysilane, for example, there can be mentioned methyltrimethoxysilane, dimethyldimethoxysilane, trimethylmethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, ethyltrimethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, isobutyltrimethoxysilane, isobutyltriethoxysilane, n-hexyltrimethoxysilane, n-hexyltriethoxysilane, cyclohexylmethyldimethoxysilane, n-octyltriethoxysilane, n-decyltrimethoxysilane, hexadecyltrimethoxysilane, and the like. Among the alkyl-containing alkoxysilanes, at least one selected from isobutyltrimethoxysilane, isobutyltriethoxysilane, n-hexyltrimethoxysilane, n-hexyltriethoxysilane, cyclohexylmethyldimethoxysilane, n-octyltriethoxysilane, n-decyltrimethoxysilane and hexadecyltrimethoxysilane is preferred, and at least one selected from n-decyltrimethoxysilane and hexadecyltrimethoxysilane is more preferred. The alkoxysilanes may be used alone or in combination of two or more.

[0053] The content of component c in the thermally conductive resin composition may be, for example, 0.1 to 2.0 parts by mass, or 0.2 to 1.0 parts by mass, relative to 100 parts by mass of the thermally conductive filler. When two or more alkoxysilanes are used in combination, the total amount thereof preferably satisfies the above content range.

[0054] <Ingredient d>

[0055] The thermally conductive resin composition of the present technology contains dimethylpolysiloxane having two or more hydroxyl groups at one end of the molecular chain as component d. Component d also functions as a dispersant. Since the thermally conductive resin composition contains component d in addition to components a to c, the kneading property is good even when an inexpensive thermally conductive filler is used as described above, and a low viscosity can be obtained. In addition, since the thermally conductive resin composition contains component d, the flexibility can be improved, and the heat resistance reliability, for example, can maintain good flexibility even in a high temperature environment. Moreover, since the thermally conductive resin composition contains component d which also functions as a dispersant, the thermally conductive filler as component b can be filled more highly, and the thermal conductivity when made into a thermally conductive sheet can be improved.

[0056] Component d has two or more hydroxyl groups at one end of the molecular chain, and may have two hydroxyl groups or three hydroxyl groups. Component d is preferably a siloxane compound represented by the following formula 1.

[0057] (Formula 1)

[0058]

[0059] In formula 1, n 1 is an integer from 0 to 100, R 1 is an alkyl group, R 2 is an alkylene chain or an oxyalkylene chain, R 3 ~R 5 Each independently represents an alkylene chain, R 6 is a hydrogen atom or an alkyl group.

[0060] In formula 1, n 1 It may be an integer from 1 to 100.

[0061] In formula 1, as R 1 The number of carbon atoms in the alkyl group may be in the range of 1 to 12, 1 to 10, 1 to 8, 1 to 6, 1 to 5, or 1 to 4. The alkyl group may be a linear alkyl group or a branched alkyl group. 1 Specific examples include methyl, ethyl, propyl and butyl.

[0062] In formula 1, R 2 In the case of an alkylene chain, the number of carbon atoms in the alkylene chain may be in the range of 2 to 12, 2 to 10, 2 to 8, 2 to 6, 3 to 10, or 4 to 10. 2 In the case of an oxyalkylene chain, the number of carbon atoms of the alkylene chain constituting the oxyalkylene chain may be in the range of 2 to 12, 2 to 10, 2 to 8, 2 to 6, 3 to 10, or 4 to 10. The alkylene chain may be linear or branched. 2 In the case of an oxyalkylene chain, the number of oxygen atoms constituting the oxyalkylene chain may be one, two or more, or in the range of one to three. 2 Specific examples include oxyalkylene chains consisting of an alkylene chain having 2 to 4 carbon atoms and an oxygen atom.

[0063] In formula 1, as R 3 ~R 5The number of carbon atoms in the alkylene chain may be in the range of 1 to 10, 1 to 8, 1 to 6, 1 to 4, or 1 to 3. The alkylene chain may be linear or branched. 3 ~R 5 As a specific example, a methylene chain can be mentioned.

[0064] In formula 1, R 6 In the case of an alkyl group, the number of carbon atoms in the alkyl group may be in the range of 1 to 10, 1 to 8, 1 to 6, 1 to 4, or 1 to 2. The alkyl group may be linear or branched. 6 Specific examples of the alkyl group include an ethyl group.

[0065] In addition, component d may be a siloxane compound represented by the following formula 2.

[0066] (Formula 2)

[0067]

[0068] In formula 2, n 2 is an integer greater than 1, R 7 It is an alkyl group.

[0069] In formula 2, n 2 It may also be an integer from 1 to 99.

[0070] In formula 2, as R 7 The number of carbon atoms in the alkyl group may be in the range of 1 to 10, 1 to 8, 1 to 6, 1 to 5, or 1 to 4. The alkyl group may be a linear alkyl group or a branched alkyl group. 7 Specific examples include methyl, ethyl, propyl and butyl.

[0071] The number average molecular weight (Mn) of component d may be in the range of 1000 to 10000, 1000 to 7000, or 1000 to 5000. The number average molecular weight of component d refers to a value measured by gel permeation chromatography (GPC) (converted into standard polystyrene molecular weight).

[0072] Examples of commercially available products of component d include FM-DA11 and FM-DA21 (produced by JNC Corporation), X-22-176DX (produced by Shin-Etsu Silicone Co., Ltd.), and X-22-176F (produced by Shin-Etsu Silicone Co., Ltd.).

[0073] In the thermally conductive resin composition, the content of component d may be 0.1% by mass or more, 0.2% by mass or more, 0.3% by mass or more, 0.4% by mass or more, or 0.5% by mass or more. In addition, in the thermally conductive resin composition, the content of component d may be 2% by mass or less, 1.5% by mass or less, 1.3% by mass or less, 1.2% by mass or less, or 1.1% by mass or less. In addition, in the thermally conductive resin composition, the content of component d may also be in the range of 0.3 to 1.2% by mass. When two or more components d are used in combination, it is preferred that the total amount satisfies the above range.

[0074] The thermally conductive resin composition may also contain components other than the above-mentioned components a to d. For example, the thermally conductive resin composition may also contain a phenolic antioxidant having an ester bond (hereinafter also referred to as "component e") as an antioxidant, or may use component e and a sulfur-based antioxidant (hereinafter also referred to as "component f") in combination as an antioxidant. In addition, the thermally conductive resin composition may also contain reinforcing materials, colorants, heat resistance enhancers, surfactants, dispersants, flame retardants, catalysts, curing retardants, degradation inhibitors, plasticizers and other additives as needed for the purpose of further improving the performance of the thermally conductive resin composition and the thermally conductive sheet.

[0075] <Ingredient e>

[0076] From the viewpoint of obtaining a thermally conductive resin composition with better heat resistance reliability, it is preferred to use a hindered phenol antioxidant as component e. A hindered phenol antioxidant refers to a compound having two sterically bulky groups (e.g., tert-butyl groups) at two ortho positions of the phenolic hydroxyl group serving as its active point. As specific examples of phenol antioxidants, antioxidants having a structure shown in the following formula 3 as a hindered phenol skeleton can be cited. The hindered phenol antioxidant preferably has one or more skeletons shown in the following formula 3, and may also have two or more skeletons shown in the following formula 3.

[0077] (Formula 3)

[0078]

[0079] In Formula 3, preferably, R 3 and R 4 Represents tert-butyl, R 5 Indicates the situation of hydrogen atom (hindered type); R 3 Represents methyl, R 4 Represents tert-butyl, R 5 Indicates the case of hydrogen atom (semi-hindered type); R 3 represents a hydrogen atom, R 4 Represents tert-butyl, R 5In the case of representing a methyl group (less hindered type). From the viewpoint of long-term thermal stability under high temperature environment, a semi-hindered type or a hindered type is preferred. In addition, the hindered phenolic antioxidant is preferably of the following structure: having three or more skeletons represented by Formula 3 in one molecule, and the three or more skeletons represented by Formula 3 are linked by a hydrocarbon group, or a group consisting of a combination of a hydrocarbon group, -O- and -CO-. The hydrocarbon group may be any of a linear, branched or cyclic type. The number of carbon atoms of the hydrocarbon group may be, for example, 3 to 8. The molecular weight of the hindered phenolic antioxidant may be, for example, 300 to 850, or 500 to 800.

[0080] In the present technology, the hindered phenol antioxidant preferably has an ester bond in its structure, that is, a hindered phenol antioxidant having an ester bond. When an addition reaction type silicone resin is used as component a, by using a hindered phenol antioxidant having an ester bond, oxidation of the addition reaction type silicone resin can be more effectively prevented, and a thermally conductive resin composition with better heat resistance reliability can be easily obtained. Examples of such hindered phenol antioxidants having an ester bond include stearyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, pentaerythritol tetrakis[3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate], 2,2'-dimethyl-2,2'-(2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diyl)dipropane-1,1'-diyl=bis[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate], and 3,9-bis[1,1-dimethyl-2-[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]ethyl]2,4,8,10-tetraoxaspiro[5,5]-undecane.

[0081] Commercially available products of hindered phenol antioxidants having an ester bond include ADK STAB AO-50 (stearyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate), ADK STAB AO-60 (pentaerythritol tetrakis[3-(3',5'-di-tert-butyl-4'-hydroxyphenyl) propionate), ADK STAB AO-80 (3,9-bis[1,1-dimethyl-2-[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]ethyl]2,4,8,10-tetraoxaspiro[5,5]-undecane) (Adeka), Irganox245, Irganox1010 (pentaerythritol tetrakis[3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate), Irganox1035 (2,2-thio[diethylbis-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]), Irganox1076 (stearyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), Irganox1135 (octyl 3-(4-hydroxy-3,5-diisopropylphenyl)propionate) (BASF), SUMILIZER GA-80 (2,2'-dimethyl-2,2'-(2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diyl)dipropane-1,1'-diyl=bis[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate]) (manufactured by Sumitomo Chemical Co., Ltd.) etc. Component e may be used alone or in combination of two or more.

[0082] When the thermally conductive resin composition contains component e, the content of component e in the thermally conductive resin composition, for example, when the content of component a in the thermally conductive resin composition is set to 100 parts by mass, can be 0.1 parts by mass or more, or 0.5 parts by mass or more, or 1 part by mass or more, or 2 parts by mass or more. In addition, in the thermally conductive resin composition, the content of component e, for example, when the content of component a in the thermally conductive resin composition is set to 100 parts by mass, can be 10 parts by mass or less, or 5 parts by mass or less, or 3 parts by mass or less, or 2 parts by mass or less. When two or more components e are used in combination, it is preferred that the total amount satisfies the above-mentioned content range.

[0083] <Component f>

[0084] From the viewpoint of obtaining a thermally conductive resin composition with better heat resistance reliability, a sulfur-based antioxidant having a thioether skeleton or a hindered phenol skeleton can be used as component f. For example, component f includes: 3,3'-ditridecyl thiodipropionate, pentaerythritol tetrakis[3-(dodecylthio)propionate], 4,6-bis(octylthiomethyl)-o-cresol, and the like.

[0085] Commercially available products of component f include: ADK STAB AO-412S, ADK STAB AO-503 (3,3'-ditridecyl thiodipropionate), ADK STAB AO-26 (all manufactured by ADEKA), SUMILIZER TP-D (manufactured by Sumitomo Chemical Co., Ltd.), Irganox 1520L (4,6-bis(octylthiomethyl)-o-cresol) (manufactured by BASF Japan), etc. Among these, tetrakis[3-(dodecylthio)propionic acid]pentaerythritol (commercially available products: ADK STAB AO-412S, SUMILIZER (registered trademark) TP-D) is preferred from the perspective of less curing hindrance. Component f may be used alone or in combination of two or more.

[0086] When the thermally conductive resin composition contains component f, it is preferably used in combination with component e, and the content of component f in the thermally conductive resin composition is preferably about the same amount as component e, or more than component e. For example, in the thermally conductive resin composition, the content of component f can be set to 0.1 mass parts or more when the content of component a in the thermally conductive resin composition is set to 100 mass parts, or it can be set to 0.5 mass parts or more, or it can be set to 1 mass part or more. In addition, in the thermally conductive resin composition, the content of component f can be set to 20 mass parts or less when the content of component a in the thermally conductive resin composition is set to 100 mass parts, or it can be set to 10 mass parts or less, or it can be set to 5 mass parts or less. When two or more components f are used in combination, it is preferred that the total amount meets the range of the above content.

[0087] The thermally conductive resin composition of the present technology has good kneading properties as described above. The kneading properties of the thermally conductive resin composition can be evaluated by the method described in the Examples described later.

[0088] The hardness of the thermally conductive resin composition of the present technology is good. In other words, the thermally conductive resin composition of the present technology can be made into a low viscosity. Therefore, the thermally conductive resin composition of the present technology can be applied using a common coating machine, for example. The hardness of the thermally conductive resin composition can be set to 22N or less, or 21N or less, or 20N or less, or 17N or less, or 15N or less, or in the range of 15 to 21N when evaluated using the method described in the embodiments described later.

[0089] <Thermal Conductive Sheet>

[0090] The thermally conductive sheet of the present technology includes a cured product of the thermally conductive resin composition described above. The thermally conductive sheet of the present technology may also be composed of a cured product of the thermally conductive resin composition described above. From the viewpoint of high thermal conductivity, the higher the thermal conductivity of the thermally conductive sheet of the present technology, the more preferred. For example, the thermal conductivity in the thickness direction (initial thermal conductivity) may be set to 4.0 W / (m·K) or more, 4.9 W / (m·K) or more, 5.0 W / (m·K) or more, 5.1 W / (m·K) or more, 5.2 W / (m·K) or more, 5.3 W / (m·K) or more, 4.9 to 6.0 W / (m·K) or more, 5.0 to 6.0 W / (m·K) or more, or 5.0 to 5.3 W / (m·K) or more. The thermal conductivity of the thermally conductive sheet may be measured by the method described in the examples described later.

[0091] The thermally conductive sheet of the present technology uses the above-mentioned thermally conductive resin composition, so the flexibility can be improved. For example, the Asker C hardness of the thermally conductive sheet of the present technology can be set to 25 or less, or 21 or less, or 20 or less, or 19 or less, or in the range of 8 to 24. The Asker C hardness of the thermally conductive sheet can be measured by the method described in the examples described below.

[0092] The thermal conductive sheet of the present technology has good heat resistance reliability. For example, the Asker C hardness after exposure to a 170°C environment for 1000 hours can be 70 or less, 59 or less, 56 or less, 49 or less, or in the range of 30 to 59. The Asker C hardness of the thermal conductive sheet can be measured by the method described in the Examples described below.

[0093] The thermally conductive sheet of the present technology can be obtained by, for example, applying a thermally conductive resin composition to a desired thickness on a release film formed of PET (polyethylene terephthalate), PEN (polyethylene naphthalate), polyolefin, polymethylpentene, cellophane, etc., and heating to cure component a. The thickness of the thermally conductive sheet can be appropriately selected according to the purpose, for example, it can be set in the range of 0.05 to 5 mm.

[0094] <Electronic equipment>

[0095] The thermally conductive sheet of the present technology can be used, for example, to be disposed between a heating element and a heat sink to produce an electronic device (thermal device) disposed between the heating element and the heat sink. The electronic device has at least a heating element, a heat sink, and a thermally conductive sheet, and may also have other components as needed.

[0096] The heating element is not particularly limited, and examples thereof include integrated circuit components such as CPU, GPU (Graphics Processing Unit), DRAM (Dynamic Random Access Memory), flash memory, transistors, resistors, and other electronic components that generate heat in the circuit. In addition, the heating element also includes components that receive optical signals such as optical transceivers in communication equipment. In addition, the heating element also includes power devices described as the use of the above-mentioned thermally conductive resin composition.

[0097] There is no particular limitation on the heat sink, and examples thereof include heat sinks used in combination with integrated circuit elements, transistors, optical transceiver housings, and the like. Materials of the heat sink and the heat sink include, for example, copper and aluminum. In addition to heat sinks and heat sinks, any heat sink that conducts heat generated by a heat source and dissipates it to the outside may be used as the heat sink, and examples thereof include heat sinks, coolers, chip pads, printed circuit boards, cooling fans, Peltier elements, heat pipes, vapor chambers, metal covers, housings, and the like. The heat pipe is, for example, a hollow structure that is cylindrical, substantially cylindrical, or flattened cylindrical.

[0098] Figure 1 1 is a cross-sectional view showing an example of a semiconductor device to which a thermally conductive sheet is applied. Figure 1 The semiconductor device 50 shown is mounted in various electronic devices and is sandwiched between a heat generating body and a heat dissipating body. Figure 1 The semiconductor device 50 shown in the figure includes an electronic component 51, a heat sink 52, and a thermally conductive sheet 1, wherein the thermally conductive sheet 1 is sandwiched between the heat sink 52 and the electronic component 51. The thermally conductive sheet 1 is sandwiched between the heat sink 52 and the heat absorbing device 53, thereby constituting a heat dissipation member for dissipating heat from the electronic component 51 together with the heat sink 52. The installation location of the thermally conductive sheet 1 is not limited to between the heat sink 52 and the electronic component 51 or between the heat sink 52 and the heat absorbing device 53, and can be appropriately selected according to the configuration of the electronic device or the semiconductor device. The heat sink 52 is formed in a square plate shape, for example, and has a main surface 52a facing the electronic component 51 and a side wall 52b erected along the outer periphery of the main surface 52a. The heat sink 52 is provided with the thermally conductive sheet 1 on the main surface 52a surrounded by the side wall 52b, and the heat absorbing device 53 is provided on the other surface 52c on the opposite side of the main surface 52a via the thermally conductive sheet 1.

[0099] Example

[0100] Hereinafter, embodiments of the present technology will be described, but it should be noted that the present technology is not limited to these embodiments.

[0101] <Preparation of thermally conductive resin composition>

[0102] The raw materials used in the preparation of the thermally conductive resin composition are as follows.

[0103] <Addition reaction type silicone resin>

[0104] An addition reaction type silicone resin formed from a mixture of an organopolysiloxane having an alkenyl group, a platinum catalyst, and an organopolysiloxane having a hydrosilyl group.

[0105] <Thermal conductive filler>

[0106] Spherical alumina (average particle size 5 to 25 μm).

[0107] Irregular shaped alumina (average particle size 0.1-50 μm).

[0108] Spherical magnesium oxide (average particle size 70-140μm).

[0109] Irregularly shaped magnesium oxide with a crystalline phase and a grain boundary phase (average particle size 60 to 130 μm).

[0110] <Alkoxysilane>

[0111] Z-6210: n-decylalkoxysilane (manufactured by Dow Toray Co., Ltd.), boiling point 115°C.

[0112] Dynasylan 9116: hexadecyl alkoxysilane (manufactured by Evonik Japan Co., Ltd.).

[0113] <Dimethyl polysiloxane having two or more hydroxyl groups at one end of the molecular chain>

[0114] FM-DA11: a one-terminal diol (manufactured by JNC Corporation), number average molecular weight (Mn) 1000 (compound represented by the following formula 4).

[0115] FM-DA21: a one-terminal diol (manufactured by JNC Corporation), number average molecular weight (Mn) 2000 (compound represented by the following formula 4).

[0116] X-22-176DX: a single-terminated diol (manufactured by Shin-Etsu Silicone Co., Ltd., a compound represented by the following formula 4).

[0117] (Formula 4)

[0118]

[0119] <Antioxidants>

[0120] AO-80: hindered phenol antioxidant (manufactured by ADEKA Corporation).

[0121] AO-412S: thioether antioxidant (manufactured by ADEKA Corporation).

[0122] <Other ingredients>

[0123] FM-0421: single-terminated methanol (manufactured by JNC Corporation).

[0124] KP-578: A graft copolymer composed of an acrylic polymer and dimethylpolysiloxane (manufactured by Shin-Etsu Silicone Co., Ltd.).

[0125] KC-6003: methanol at both ends (manufactured by Shin-Etsu Chemical Co., Ltd.).

[0126] FM-9915: silanol at both ends (manufactured by JNC Corporation).

[0127] ZS-90: heavy metal passivator (manufactured by ADEKA Corporation).

[0128] <Preparation of thermally conductive resin composition>

[0129] A thermally conductive resin composition formed of the components shown in Table 1 was prepared. A self-rotating revolution type stirrer was used for stirring, and the speed was set to 1200 rpm. In Table 1, unless otherwise specified, the amount of each component described in the column of the embodiment or comparative example is expressed in parts by mass. In Table 1, the "mass parts (a)" column represents the total mass of the components constituting the thermally conductive resin composition. In addition, in Table 1, the "filler content (mass parts) (b)" column represents the total mass of the thermally conductive filler in the thermally conductive resin composition. In addition, in Table 1, the "filler mass % (c) = (b) / (a)" column represents the proportion (mass %) of the thermally conductive filler in the thermally conductive resin composition. In addition, in Table 1, the "irregular shape filler content (mass parts) (d)" represents the total mass of irregularly shaped thermally conductive fillers in the thermally conductive resin composition. In Table 1, the column "Mass % of irregular shaped filler in filler (e) = (d) / (b)" shows the ratio (mass %) of the total mass of irregular shaped thermally conductive fillers in the thermally conductive resin composition to the total mass of the thermally conductive fillers.

[0130] <Production of thermally conductive sheets>

[0131] The thermally conductive resin composition was sandwiched between a 100 μm thick PET base film subjected to a release treatment and a 30 μm thick PET cover film subjected to a release treatment, and passed through a bar coater so as to have a thickness of 2 mm to obtain a thermally conductive sheet precursor. The precursor was heated at 80° C. for 6 hours to be cured to obtain a thermally conductive sheet.

[0132] <Mixability>

[0133] The kneadability of the thermally conductive resin composition was determined visually. Specifically, it was determined visually whether the composition after kneading had gloss, bubbles, and agglomeration of particles. The kneadability of the thermally conductive resin composition was good, i.e., the composition after kneading had gloss, no bubbles, and no agglomeration of particles, and was evaluated as OK, and the other cases were evaluated as NG. The results are shown in Table 1.

[0134] <Hardness>

[0135] Using a tabletop physical property tester (manufactured by Yamaden Co., Ltd., model: TPU-2D) in the texture measurement mode, under the conditions of plunger (cylindrical, diameter 16 mm, height 25 mm, contact area diameter 16 mm, sample height 13 mm), gap setting: 2.0 mm, and measurement speed 5 mm / sec, the maximum load value (N) of the thermally conductive resin composition was evaluated as the hardness of the thermally conductive resin composition. The results are shown in Table 1. From the perspective of coating properties, the hardness of the thermally conductive resin composition is preferably 22N or less.

[0136] <Initial thermal conductivity>

[0137] The thermal resistance measuring device based on ASTM-D5470 was used and a load of 1 kgf / cm was applied. 2 The initial thermal conductivity (W / (m·K)) of the thermal conductive sheet in the thickness direction was measured. The sheet temperature during the measurement was 25° C. The results are shown in Table 1. In practical terms, the initial thermal conductivity of the thermal conductive sheet is preferably 4.0 W / (m·K) or more.

[0138] <Flexibility (ASKER C hardness)>

[0139] As the softness of the thermal conductive sheet, the Asker C hardness of the thermal conductive sheet was measured according to the specification of JIS K7312. Specifically, the Asker C hardness was measured at a temperature of 25°C using a hardness meter (manufactured by Kobunsu Keiki Co., Ltd.; trade name "Asker Rubber Hardness Meter Type C"). The results are shown in Table 1. From the viewpoint of adhesion and workability, the Asker C hardness of the thermal conductive sheet is preferably 25 or less.

[0140] <Heat resistance reliability (ASKER C hardness)>

[0141] As the heat-resistant reliability of the thermally conductive sheet, the ASKER C hardness of the thermally conductive sheet after the super heat resistance test at 170°C for 1000 hours was measured. That is, the ASKER C hardness of the thermally conductive sheet after being exposed to an environment at 170°C for 1000 hours was measured according to the specification of JIS K7312. Specifically, under the condition of a temperature of 25°C, the thermally conductive sheet after being exposed to an environment at 170°C for 1000 hours was left to stand at 25°C for 1 hour, and the ASKER C hardness was measured using a hardness meter (manufactured by Polymer Meter Co., Ltd.; trade name "ASKER Rubber Hardness Meter Type C"). The results are shown in Table 1. From the viewpoint of maintaining thermal conductivity and flexibility, the ASKER C hardness of the thermally conductive sheet after being exposed to an environment at 170°C for 1000 hours is preferably 70 or less, and more preferably 59 or less.

[0142] [Table 1]

[0143]

[0144] It can be seen that in Examples 1 to 8, the heat-resistant reliability is good by using the heat-conductive resin composition containing an addition reaction type silicone resin, a heat-conductive filler, an alkoxysilane, and a dimethyl polysiloxane having two or more hydroxyl groups at one end of the molecular chain. Specifically, it can be seen that the heat-conductive sheets using the heat-conductive resin compositions of Examples 1 to 8 have good flexibility even when placed at high temperatures.

[0145] In addition, it can be seen that the thermally conductive sheets using the thermally conductive resin compositions of Examples 1 to 8 also have good initial thermal conductivities. Furthermore, it can be seen that the thermally conductive resin compositions of Examples 1 to 8 also have good hardness. Furthermore, it can be seen that the thermally conductive resin compositions of Examples 1 to 8 also have good kneading properties.

[0146] It is known that in Comparative Examples 1 to 4 and 6, since the thermally conductive resin composition containing an addition reaction type silicone resin and an alkoxysilane and not containing a dimethylpolysiloxane having two or more hydroxyl groups at one end of the molecular chain is used, it is difficult to achieve good heat resistance reliability. Specifically, it is known that the thermally conductive sheets using the thermally conductive resin compositions of Comparative Examples 1 to 4 and 6 have poor flexibility when placed at high temperatures.

[0147] It is also found that the thermally conductive resin composition of Comparative Example 1 is difficult to improve heat resistance reliability and has poor hardness. It is also found that the thermally conductive sheet using the thermally conductive resin composition of Comparative Example 1 has poor flexibility before being placed at high temperatures.

[0148] Furthermore, it was found that in Comparative Example 2, the hardness of the thermally conductive resin composition was not good.

[0149] Furthermore, it is found that the kneading property of the thermally conductive resin composition is not good and it is difficult to produce a thermally conductive sheet in Comparative Example 3. Therefore, it is found that in Comparative Example 3, evaluation other than the kneading property of the thermally conductive resin composition cannot be performed.

[0150] Furthermore, it is found that in Comparative Example 4, the flexibility of the thermal conductive sheet before being placed at high temperature is not good.

[0151] Furthermore, it was found that the hardness of the thermally conductive resin composition was not good in Comparative Example 6. Furthermore, it was found that the flexibility of the thermally conductive sheet before being placed at a high temperature was not good in Comparative Example 6.

[0152] It is known that in Comparative Example 5, a thermally conductive resin composition containing an addition reaction type silicone resin, a thermally conductive filler, and dimethyl polysiloxane having two or more hydroxyl groups at one end of the molecular chain, and not containing alkoxysilane, is used, so it is difficult to make the heat resistance reliability good. Specifically, it is known that the thermally conductive sheet using the thermally conductive resin composition of Comparative Example 5 has poor flexibility when placed at high temperature. In addition, it is known that in Comparative Example 5, the flexibility of the thermally conductive sheet before being placed at high temperature is also poor. Moreover, it is known that in Comparative Example 5, the initial thermal conductivity of the thermally conductive sheet is also poor.

Claims

1. A thermally conductive resin composition comprising: Addition reaction type silicone resin, Thermally conductive fillers, Alkoxysilane, and A dimethyl polysiloxane having two or more hydroxyl groups at one end of the molecular chain.

2. The thermally conductive resin composition according to claim 1, wherein The dimethyl polysiloxane is a siloxane compound represented by the following formula 1: Formula 1 In formula 1, n 1 is an integer from 0 to 100, R 1 is an alkyl group, R 2 is an alkylene chain or an oxyalkylene chain, R 3 ~R 5 Each independently represents an alkylene chain, R 6 is a hydrogen atom or an alkyl group.

3. The thermally conductive resin composition according to claim 1, wherein The dimethyl polysiloxane is a siloxane compound represented by the following formula 2: Formula 2 In formula 2, n 2 is an integer greater than 1, R 7 It is an alkyl group.

4. The thermally conductive resin composition according to claim 1 or 2, wherein The thermally conductive filler contains a thermally conductive filler having an irregular shape.

5. The thermally conductive resin composition according to claim 4, wherein The thermally conductive filler contains magnesium oxide.

6. The thermally conductive resin composition according to claim 1 or 2, wherein The thermally conductive resin composition further contains a phenolic antioxidant having an ester bond.

7. The thermally conductive resin composition according to claim 1 or 2, wherein The thermally conductive resin composition further contains a sulfur-based antioxidant. 8 . A thermally conductive sheet comprising a cured product of the thermally conductive resin composition according to claim 1 or 2 .

9. The thermally conductive sheet according to claim 8, wherein The thermal conductivity is 4.0 W / (m·K) or more.

10. The thermally conductive sheet according to claim 8, wherein ASKER C hardness is 8~24.

11. The thermally conductive sheet according to claim 8, wherein The Asker C hardness after exposure to 170°C for 1000 hours is 30-59.

Citation Information

Patent Citations

  • Heat-conductive silicone potting composition, and cured product of the same

    JP2021113290A

  • Thermally conductive silicone composition and cured product thereof

    JP2021176945A

Cited By

  • Thermal interface materials having high recovery and high stable recovery reliability

    WO2026193747A1